2015
DOI: 10.1039/c5ta04235f
|View full text |Cite
|
Sign up to set email alerts
|

Perovskites for photovoltaics: a combined review of organic–inorganic halide perovskites and ferroelectric oxide perovskites

Abstract: REVIEWThis journal is © The Royal Society of Chemistry 2015 J. Mater. Chem. A 1Over the past few years, very interestingly, two subclasses of perovskitesorganic-inorganic halide perovskites and ferroelectric oxide perovskites, have simultaneously become the hotspots in the research field of photovoltaics. Organic-inorganic halide perovskites have launched a new era of low-cost, high-efficiency solar cells, due to their easy solution processability and superior optical and electrical properties for the photovol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
173
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(173 citation statements)
references
References 193 publications
(435 reference statements)
0
173
0
Order By: Relevance
“…Further increasing the doping concentration beyond 1wt%, however,r esulted in decreasedc onductivity (Figure 1b). [29][30][31] Given that the surfacec overage of the HTL on top of the perovskite film plays an importantr olei np erformance optimi-zation of n-i-p type PSCs, [2,4,10] AFM topographici mageso ft he FAPbI 3 perovskite films with and without PEDOT films were also studied. As shown in Figure 2, PEDOTf ilms with Mo(tfd-COCF 3 ) 3 doping concentration below 1wt% displayed uniform and smooth morphology with root-mean-square (rms) roughness of approximately 3.7 nm, suggesting high miscibility between Mo(tfd-COCF 3 ) 3 and PEDOT.H igher doping concentration caused greater surface roughness (rms roughness > 12 nm) with more pronounced phase-separated domains (Figure2), which can impede the carriert ransport within the film.…”
Section: Resultsmentioning
confidence: 99%
“…Further increasing the doping concentration beyond 1wt%, however,r esulted in decreasedc onductivity (Figure 1b). [29][30][31] Given that the surfacec overage of the HTL on top of the perovskite film plays an importantr olei np erformance optimi-zation of n-i-p type PSCs, [2,4,10] AFM topographici mageso ft he FAPbI 3 perovskite films with and without PEDOT films were also studied. As shown in Figure 2, PEDOTf ilms with Mo(tfd-COCF 3 ) 3 doping concentration below 1wt% displayed uniform and smooth morphology with root-mean-square (rms) roughness of approximately 3.7 nm, suggesting high miscibility between Mo(tfd-COCF 3 ) 3 and PEDOT.H igher doping concentration caused greater surface roughness (rms roughness > 12 nm) with more pronounced phase-separated domains (Figure2), which can impede the carriert ransport within the film.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Perovskites are materials with stoichiometry ABX 3 that crystallize in the well-known structure named for crystallographer Lev Perovski. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Perovskites are materials with stoichiometry ABX 3 that crystallize in the well-known structure named for crystallographer Lev Perovski.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Perovskites are materials with stoichiometry ABX 3 that crystallize in the well-known structure named for crystallographer Lev Perovski. This provides octahedral coordination of every B-site (BX 6 ) and cuboctahedral coordination on the A-site (AX 12 ). In a cubic unit cell centered around an A-type ion, B-type ions occupy the corners, with X-type ions at the centers of all unit cell edges.…”
Section: Introductionmentioning
confidence: 99%
“…By comparison, CH 3 NH 3 PbI 3 has a valence band maximum at 5.43 eV. 88 (CH 3 NH 3 ) 3 Bi 2 I 9 , with a valence band maximum at 5.9 eV, is one of the most commonly investigated bismuth-based compounds. 3 Shin et al 77 recently demonstrated that the efficiency of (CH 3 NH 3 ) 3 replacing spiro-OMeTAD (2,2 ,7,7 -tetrakis(N,N-di-p-methoxyphenyl-amine)9,9 -spirobifluorene), an organic hole transport layer commonly used in lead-halide perovskite devices, with PIF8 TAA (poly-indenofluoren-8-triarylamine), which has a deeper highest occupied molecular orbital (HOMO) level which is more closely aligned with the valence band maximum of (CH 3 NH 3 ) 3 Bi 2 I 9 .…”
Section: Contacts and Device Performance For Bismuth-based Photovmentioning
confidence: 99%